Semiotics analysis of symbol (emoji) that found in the captions of @brianimanuel instagram account - Jannah, Roikhatul; Maharani, Putu Devi; Winarta, I.B. Gde Nova (Journal of Language and Applied Linguistics, 2022)
The study is focused on find out the total amount of symbol (emoji) and the meaning of symbol (emoji) that found in the captions of @brianimanuel Instagram account. This study is used theory proposed by Charles Sanders Peirce about semiotic and used semiosis process. This study took the data from the captions of @brianimanuel in his Instagram Post that used emoji from 27 Sept 2019 – 15 Feb 2021. In this study, the writers used observation procedure descriptive-qualitative method for analyzing the data. In addition, for presented the data, the writer used an informal method. This study found there are 73 total amount of emoji and 73 meaning of symbol (emoji) that found in the 55 captions of @brianimanuel in his Instagram Post.